PINE PITCH CANKER (FUSARIUM CIRCINATUM) HISTORY, EVOLUTION, EPIDEMIOLOGY AND MANAGEMENT STRATEGIES - Flores-Pacheco, J. A. (Nexo Revista Científica, 2017)
The disease called Pine Pitch Canker is caused by the fungus ascomycete Fusarium circinatum Nirenberg et O'Donnell (teleomorph= Gibberella circinata Nirenberg et O'Donnell). It affects numerous species of conifers and to date has presence in all the continents of the world, except Antarctica. Due to global climatic and environmental variations that have favored the biological dispersion range of the disease, together with the international trade in wood and its derivatives with insufficient quarantine measures, the fungus currently threatens to spread to areas free of infection. In areas where the presence of the disease has already been confirmed, significant economic losses are reported in nurseries, forest seedlings, wild and commercial plantations of different species of conifers. This must be complemented by the no less important ecosystem loss caused by the instability of forests and ecological niches highly sensitive to floristic variations. It is currently considered the most important pathology in the world of conifers, both wild and commercial, and has no curative treatment, so efforts are focused on preventive treatment. Within the scientific field, the research on genetic resistance of the host and the use of biological controllers that promise significant results stand out.